Good taste : a novel in search of great food - Scott, Caroline (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"With delectable prose, a sharp heroine ahead of her time, and an adventure across the English countryside in search of great food, Good Taste is the perfect historical novel for fans of Dear Mrs. Bird and The Guernsey Literary and Potato Peel Pie Society. You can tell a lot about a person from what they like to eat... England in 1932 is in the grip of the Great Depression. Stella Douglas, author of a much-loved but not very successful biography, is a bit depressed herself. When she's summoned to see her editor in London, she expects her writing career is over before it's even started. But much to her surprise, she is being commissioned to write a history of English food. It's to be quintessentially English and intended to lift the spirits of the nation. There's just one problem: a lot of English food is actually quite terrible (and anything good is usually imported from elsewhere). So Stella travels across England in hopes of discovering a hidden culinary gem. What she discovers is oatcakes and gravy and lots and lots of potatoes. But when her car breaks down midjourney and the dashing and charismatic antiques dealer Freddie springs to her rescue, she is led in a very different direction... Full of wit, life, and--against all odds--delicious food, Good Taste is a story of discovery and one woman's desire to make her own way as a modern woman"--